Recommendations for Donor and Recipient Selection and Risk Prediction: Working Group Report From the ILTS Consensus Conference in DCD Liver Transplantation. Issue 9 (19th August 2021) - Schlegel, Andrea; Foley, David P.; Savier, Eric; Flores Carvalho, Mauricio; De Carlis, Luciano; Heaton, Nigel; Taner, C. Burcin
Abstract : Supplemental Digital Content is available in the text. Abstract : Although the utilization of donation after circulatory death donors (DCDs) for liver transplantation (LT) has increased steadily, much controversy remains, and no common acceptance criteria exist with regard to donor and recipient risk factors and prediction models. A consensus conference was organized by International Liver Transplantation Society on January 31, 2020, in Venice, Italy, to review the current clinical practice worldwide regarding DCD-LT and to develop internationally accepted guidelines. The format of the conference was based on the grade system. International experts in this field were allocated to 6 working groups and prepared evidence-based recommendations to answer-specific questions considering the currently available literature. Working group members and conference attendees served as jury to edit and confirm the final recommendations presented at the end of the conference by each working group separately. This report presents the final statements and recommendations provided by working group 2, covering the entire spectrum of donor and recipient risk factors and prediction models in DCD-LT. Abstract :